Proteinograma de leite de vacas com mastite subclínica em função do escore de células somáticas e de microrganismos isolados e identificados por microbiologia convencional - Freitas, Fernanda Antunha de (2017)
Intramammary infections can be triggered by a large number of etiologic agents and may lead to changes in the mammary gland parenchyma, composition of milk and reduction of milk production. The aim of the present study was to evaluate the electrophoretic profile of cow milk proteins by the analysis of microfluidic electrophoresis lab-on-a-chip and its alterations in relation to milk samples with different SCC and the presence of pathogenic microorganisms. A total of 101 milk samples were collected from cows from two dairy farms located in the state of Goiás. Microbiological analyzes, somatic cell counts, centesimal composition and microfluidic electrophoresis were performed. For the correlation test between the protein profile and the SCC the samples were stratified into five groups of somatic cells scores. The data were analyzed using descriptive statistics through the analysis of variance and graphical representations. There was a significant increase in the value of the protein component in relation to the SCS 1 and 3, 1 and 4 and 1 and 5. It was also possible to observe statistical difference in the results of the Lactose component when comparing SCS 1 and 3 and SCS 3 and 4. The evaluation of the variable "Concentration" of milk proteins was possible to observe differences in the concentration values of SCS. Statistical difference was also observed for concentration of α-LA when compared SCS 1,2 and 3 to SCS 5; For IgG, SCS samples 4 and 5 showed different concentrations of SCS samples 1,2 and 3; the LF protein showed different results among samples from the SCS 1 and 5. The microorganisms identified were Staphylococcus spp. Negative Coagulase, Arcanobacterium pyogenes, Streptococcus spp., Staphylococcus aureus, Bacillus spp. and yeast. There is no statistical evidence that the mean concentration of the proteins present in milk samples is different between any groups of samples with different microorganisms evaluated. In the comparison between the concentrations of each protein expressed in each group of samples, a statistical difference was observed in the concentration of α-lactalbumin between samples from the yeast group and samples without bacterial growth. It was concluded that whey proteins of high abundance have their concentration decreased with the occurrence of mastitis; Defense proteins such as Lactoferrin, Lactoperoxidase, IgG and IgM have their concentration increased when comparing milk samples from cows with subclinical mastitis and milk samples from healthy cows; Lactoferrin and IgG proteins are potential targets for identifying cows with subclinical mastitis in milk samples and may be considered biomarkers. It was also concluded that intramammary infections caused by the microorganisms identified in the present study do not alter the concentration of whey proteins of lactating cows; Milk samples with high SCC may present negative results for microbiological culture; The SCN showed higher frequency of isolation in milk samples from lactating cows, revealing opportunistic and saprophytic characteristics; And infection of the mammary gland caused by yeast causes a significant increase of the α-lactalbumin protein.